From the hymnal to the worship industry: a study on the transformation of religious music - Navarro, Carlos Garma (2000)
Music is a very important part of Mexican Pentecostalism. Mexican Pentecostal music has undergone remarkable changes in the last decades. Today hymn production for the congregation’s local consumption has led the way to the “praising industry” (industria de la alabanza) phenomena, as refer to by Pentecostal bishop M. Gaxiola, characterized by the production of sound and video tapes as well as artist’s road tours. In order to understand such a shift it is useful to ask about the uses of the actors.